MITO, SACRALIDADE E TIRANIA NO ÉDIPO TIRANO - Marshall, Francisco (Organon, 2012)
As the most accomplished version of the Greek myth of Oedipus, the tragedy OedipusTyrannus of Sophocles is the basic source for the understanding of many problems in the interpretation ofcultures (Greek and others). Nevertheless, it’s a document strongly related to its own social and historicalcontext. Aiming to reach cardinal meanings of this masterpiece, hereby we will do a close reading of theSecond Stasimon (vv. 863-910), considering its main interpretative problems and perceiving the manyways it connects the religious ethics to the idea of social and political order. Hence we can also explainthe meaning of tyranny in this tragedy as well as in its communicative context.